The occurrence of a palaeo‐lithification front in an overpressured basin (Chalk Group)—Timing from clumped isotopes and seismic stratigraphic analysis. (18th March 2022) - Smit, F. W. H.; Stemmerik, L.; Smith, M. E.; Staudigel, P. T.; Lüthje, M.; Mathiesen, A.; van Buchem, F. S. P.; Swart, P. K.
Abstract: This study proposes a unique workflow to unravel complex burial diagenetic histories of overpressured basins based on the integration of seismic and well log data, biostratigraphy, petrography, clumped isotope analyses and basin modelling. This approach is demonstrated with an example from the Chalk Group in the Danish Central Graben, where a seismic‐scale palaeo‐lithification front has been observed and studied in detail to elucidate the timing of the establishment of overpressured conditions and its relation to changing diagenetic activity. The palaeo‐lithification front separates high‐porosity chalks above, that dominantly underwent mechanical compaction and contact cementation, from low‐porosity chalk below, that dominantly underwent severe pressure dissolution and pore‐filling cementation. Analysis of chalk buried under hydrostatic conditions shows a strikingly similar lithification front between 1000 and 1200 m burial, much shallower than the lithification front in the Danish Central Graben at a current depth between 2100 and 2400 m below seafloor. The discrepancy of 1200 m is due to the establishment of overpressured conditions that limited the increase in effective stress as burial continued, finally halting burial compaction when formation fluids started to carry the lithostatic weight. Basin modelling data indicate that this occurred at the end of the Oligocene for large parts of the Danish Central Graben, which is much earlier than the Middle Miocene timing that is currently assumed. The results imply a regional occurrence of a relict lithification front in the North Sea Basin, its position guided by stratigraphy, but mainly dependent on the maximum effective stress experienced during its burial history. The study shows that the porosity bipartition is a remnant of the past and not from ongoing compaction as has previously been suggested. Since it was established before the thermal maturity of the main source rocks, chalk below the lithification front must have formed a sealing unit during hydrocarbon migration. The recognition of the lithification front is also of importance to velocity modelling and depth‐conversion since a non‐linear increase between velocity and depth is expected across this boundary. The methodology may be applied in other overpressured basins where the diagenetic state of reservoir rocks at the end of hydrostatic conditions must be constrained. Abstract : Based on the integration of seismic and well log data, biostratigraphy, petrography, clumped isotope analyses, and basin modelling, a burial model is proposed for the Chalk Group that experienced hydrostatic and subsequently overpressured conditions, which resulted in the recognition of a palaeo‐lithification front.